2017
DOI: 10.3389/fpls.2017.00764
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Dependent Interaction of Lentil Lines with Ascochyta lentis

Abstract: Ascochyta blight of lentil is a prevalent disease in many lentil producing regions and can cause major yield and grain quality losses. The most environmentally acceptable and economically profitable method of control is to develop varieties with high levels of durable resistance. Genetic studies to date suggest that ascochyta blight resistance genes (R-gene) in lentil lines CDC Robin, ILL 7537, 964a-46, and ILL 1704 are non-allelic. To understand how different R-genes manifest resistance in these genotypes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 69 publications
(88 reference statements)
12
23
0
Order By: Relevance
“…These results provide further evidence of the presence of different defence mechanisms among lentil genotypes. In the present work, and as previously reported (Sambasivam et al, 2016, Sari et al, 2017, conidial germination of both isolates was significantly higher on the attached leaflets of the susceptible genotype ILL6002 than on the resistant genotype ILL7537. However, lowest conidial germination percentages were observed on the leaflets of the genotype ILWL180 for both isolates.…”
Section: Arabidopsis Thaliana Leading To Easier Penetration and Aggresupporting
confidence: 91%
See 3 more Smart Citations
“…These results provide further evidence of the presence of different defence mechanisms among lentil genotypes. In the present work, and as previously reported (Sambasivam et al, 2016, Sari et al, 2017, conidial germination of both isolates was significantly higher on the attached leaflets of the susceptible genotype ILL6002 than on the resistant genotype ILL7537. However, lowest conidial germination percentages were observed on the leaflets of the genotype ILWL180 for both isolates.…”
Section: Arabidopsis Thaliana Leading To Easier Penetration and Aggresupporting
confidence: 91%
“…As with previous reports, pre-penetration events were genotype-specific (Sambasivam et al, 2016, Sari et al, 2017 with both isolates exhibiting differential germination percentages, germ tube lengths, as well as timing and percentage of appressoria formation on both the attached and detached leaflets of the three genotypes assessed. These results provide further evidence of the presence of different defence mechanisms among lentil genotypes.…”
Section: Arabidopsis Thaliana Leading To Easier Penetration and Aggresupporting
confidence: 79%
See 2 more Smart Citations
“…Histological differences in the reaction to A . lentis infection and induction of the two major defense signaling pathways employing SA and JA were reported for the lentil genotypes CDC Robin and 964a-46, which carry non-allelic resistance genes for partial resistance to ascochyta blight in comparison with the susceptible check Eston [ 29 ]. This study indicated that cell death inhibition is possibly a mechanism of resistance in CDC Robin, whereas 964a-46 underwent cell death similar to the susceptible control Eston.…”
Section: Introductionmentioning
confidence: 99%